Assessment of Periodontal Health Status in Type-2 Diabetes Mellitus Patients with Chronic Periodontitis: An Observational Study - Shaik, Shazia Begum; Ramanarayana, Boyapati; Dhulipalla, Ravindranath; Kumar, Katuri Kishore; Lakshmikanth, Kolaparthy; NagaRani, Jayavaram; Bhochhibhoya, Amar (Journal of Nepalese Prosthodontic Society, 2026)
Introduction: Periodontitis is an immuno-inflammatory chronic condition which shows signs and symptoms eventually leading to tooth mobility and loss. Systemic diseases such as diabetes remain the important risk factors for periodontitis. Diabetic patients are in higher risk when compared to nondiabetic patients There is a strong association between glycemic levels and periodontitis, making it an important factor to consider when clinically assessing a patient’s dental health. Therefore, this study aimed to study the impact of blood glycemic levels, as determined by HbA1c levels, on several clinical and radiographic indicators in patients with Type 2 Diabetes Mellitus and chronis periodontitis. Methods: 159 subjects with chronic periodontitis and Type 2 Diabetes Mellitus were selected and sent for HbA1C levels and Orthopantamogram Clinical examination such as recording of Probing Pocket Depth (PPD), Clinical attachment loss (CAL), number of teeth lost, alveolar bone loss in patients was performed. The patients were categorized into good, moderate and poor based on glycaemic control. The clinical parameters such as Gingival Index (GI) and Plaque Index (PI) were also assessed. Results: All the parameters i.e., PI, GI, PD, CAL showed significant reduced values in good glycaemic controlled patients. These include 1.54±0.88, 1.24±0.86, 3.16±1.05 mm, 3.24±1.14 mm for PI, GI, PPD and CAL respectively. Similarly, Schei score and number of teeth lost were higher in poor glycaemic control patients. Conclusion: This study confirmed that poor glycemic control patients have severe periodontitis. It is very important for clinicians such as endocrinologists and diabetologists to refer diabetic patients with gingival inflammation, partially edentulism to dentists. Diabetes and periodontitis managementprotocols should use interdisciplinary collaboration methods. The goal of this team approach would be to identify diabetes individuals who are at risk for periodontal disease (as part of a pre-diabetic screening at the dentist office) and vice versa.